HIDROGENASI CO2 MENJADI METANOL DENGAN MENGGUNAKAN KATALIS ZEOLIT ALAM, ZEOLIT SINTESA ZSM-5 DAN KATALIS SINTESA Cu/ZnO/Al2O3 - Yanna Syamsuddin (Purifikasi, 2008)
The effect of CO2 to the environment can be reduced by converting the gas into valuable product. One of the alternative ways to make use of CO2 is by hydrogenation into methanol by catalyst. Research on hydrogenation of CO2 into methanol over natural zeolite, synthesized zeolite ZSM-5 and synthesized Cu/ZnO/Al2O3 catalysts had been done. The synthesized Cu/ZnO/Al2O3 catalyst was prepared by impregnation method, while the synthesized ZSM-5 was prepared by gel permeation method. Components of the catalyst were characterized by XRD method. Catalyst activity was examined by reacting hydrogen, carbon dioxide and nitrogen with the ratio of 6 : 3 : 1. The research was conducted at temperature of 300-500oC, with the reaction time of 2 h and the catalyst loading of 1 g with the variation of catalyst used, natural zeolite, synthesized ZSM-5 and synthesized Cu/ZnO/Al2O3. The results of catalyst characterization showed that almost all of the characteristic peaks of natural zeolite were alumina and silica and component of Cu/ZnO/Al2O3 were Cu, CuO, ZnO, and Al2O3. The crystallinity of ZSM-5 was low. Results of hydrogenation reaction showed that the highest CO2 conversion, methanol selectivity and methanol yield were 92%, 68% and 65%, respectively, obtained from the reaction over natural zeolite at reaction temperature of 500oC. Natural zeolite showed higher activity than synthesized ZSM-5 and Cu/ZnO/Al2O3.